The Role of Teachers in Utilizing Information Technology and Computers for Early Childhood Education Learning - Aus Arief Ikhwani Hakim; Dina Ayustina (LP3M STAI MA'ARIF MAGETAN, 2024)
Along with the times, technology in its development certainly brings changes to life, especially in the world of education which will also continue to develop. This article aims to find out the role of educational technology in improving the quality of education in this progressive era. So it is hoped that educational technologists will no longer feel doubt and are interested in adapting and being able to utilize technology with all its benefits in educational life. In writing this article, we use the qualitative Descriptive Method, where the techniques in collecting data for this research use interviews, observations, and documentation. Based on the discussion, it can be concluded that educational technology was created to solve learning problems by facilitating and providing new alternatives and innovations in the world of education. That way, educational technology can make it easier to achieve educational goals